An audit of uncertainty in multi-scale cardiac electrophysiology models. (25th May 2020) - Clayton, Richard H.; Aboelkassem, Yasser; Cantwell, Chris D.; Corrado, Cesare; Delhaas, Tammo; Huberts, Wouter; Lei, Chon Lok; Ni, Haibo; Panfilov, Alexander V.; Roney, Caroline; dos Santos, Rodrigo Weber
Abstract : Models of electrical activation and recovery in cardiac cells and tissue have become valuable research tools, and are beginning to be used in safety-critical applications including guidance for clinical procedures and for drug safety assessment. As a consequence, there is an urgent need for a more detailed and quantitative understanding of the ways that uncertainty and variability influence model predictions. In this paper, we review the sources of uncertainty in these models at different spatial scales, discuss how uncertainties are communicated across scales, and begin to assess their relative importance. We conclude by highlighting important challenges that continue to face the cardiac modelling community, identifying open questions, and making recommendations for future studies. This article is part of the theme issue 'Uncertainty quantification in cardiac and cardiovascular modelling and simulation'.